Nagroda im. Kościelskich 1962 - Busza, Andrzej (Wydawnictwo Uniwersytetu Rzeszowskiego, 2011)
The text is a remembrance account on the author’s being awarded the literary prize of the Kościelscy Foundation in 1962.
Keywords: Busza Andrzej; Nagroda Fundacji im. Kościelskich